World data on education 1993-1994 (International Bureau of Education GenevaCH, 1996)
Comprises the reports on developments in education presented by Member States to the 44th session of the International Conference on Education, held in Geneva in 1994. Includes also the report presented at the 43rd sesion.
Keywords: EDUCATION